Colletotrichum siamense and Pestalotiopsis jesteri as potential pathogens of new rubber leaf spot disease via detached leaf assay - Sharifah Aliya, Syed Sagaff; Nusaibah, Syd Ali; Mohmad Mahyudin, Murnita; Wong, Mui Yun; Yusop, Mohd Rafii (Springer, 2022)
The rubber tree (Hevea brasiliensis) is one of the important crops as it is the main source of natural rubber (NR) worldwide. However, rubber trees are prone to a wide range of foliar diseases, which leads to a declining latex yield. At present, a new leaf spot disease of rubber trees has been identified in five rubber-producing countries namely Indonesia, India, Malaysia, Thailand, and Sri Lanka. This is the first report of the disease, with infected leaves exhibiting a circular spot with a brown necrotic lesion. To date, no research has confirmed the real causal pathogen of the disease. Researchers from the affected countries claimed that either Colletotrichum sp. or Pestalotiopsis sp. could be the primary causal pathogen of this new leaf spot disease. This study aimed to determine the primary fungal pathogen that causes leaf spot symptoms on matured rubber leaves via in vitro pathogenicity tests using the most frequently isolated fungi from the symptomatic leaves of rubber. The severity of the infection was graded based on the size of the lesion. Eight treatments were designed for this in vitro pathogenicity test. The wounding technique produced a necrotic lesion on the surface of the leaves as early as 3 days after inoculation. Wounded leaves inoculated with both mycelial plugs of Colletotrichum siamense and Pestalotiopsis jesteri produced mean lesion lengths of 12.1 mm ± 1.15a and 6.08 mm ± 0.04b, respectively. However, both C. siamense and P. jesteri were unable to initiate an infection in non-wounded leaves in a short period of time when the host outer barriers were intact. These findings demonstrate that disease occurrence in nature can be facilitated by primary abiotic and biotic stresses for the causal pathogen to invade the host cell. From the results obtained, P. jesteri could be the opportunistic pathogen that infects rubber leaves when they are wounded and is associated with C. siamense. Opportunistic pathogens will cause secondary infections and increase the severity of the disease. It could be concluded that C. siamense may be the primary causal pathogen and P. jesteri as the secondary pathogen of the new leaf spot disease of rubber.